Analysis of Vibration Characteristics for a Rotor-Bearing System Using Distributed Spring and Damper Model - D. C. Han; S. H. Choi; Y. H. Lee (International Journal of Rotating Machinery)
In this paper, we modelled the journal beatings as distributed springs and dampers to investigate the influence of beating width on the vibration characteristics of a rotor-beating system. A quadratic function is used as a shape function for hydrodynamic journal bearings. And a trapezoidally or a quadratically distributed model is used as a shape function for hydrostatic journal bearings. A finite element method is applied for analyzing the vibration characteristics of a rotor-bearing system.